Peptide strand length controls the energetics of self‐assembly and morphology of β‐sheet fibrils. Issue 1 (31st January 2018) - Davies, Robert P. W.; Liu, Binbin; Maude, Steven; Carrick, Lisa M.; Nyrkova, Irina; McLeish, Tom C.; Harris, Sarah A.
Abstract: Self‐assembling peptides can be used as versatile, natural, and multifunctional building blocks to produce a variety of well‐defined nanostructures, materials and devices for applications in medicine and nanotechnology. Here, we concentrate on the 1D self‐assembly of de novo designed Px‐2 peptide β‐strands into anti‐parallel β‐sheet tapes and higher order aggregates. We study six members of the Px‐2 family, ranging from 3 amino acids (aa) to 13 aa in length, using a range of complementary experimental techniques, computer simulation and theoretical statistical mechanics. The critical concentration for self‐assembly (c*) is found to increase systematically with decreasing peptide length. The shortest peptide found to self‐assemble into soluble β‐tapes in water is a 5 amino acid residue peptide. These investigations help decipher the role of the peptide length in controlling self‐assembly, aggregate morphology, and material properties. By extracting free energies from these data using a statistical mechanical analysis and combining the results with computer simulations at the atomistic level, we can extract the entropy of association for individual β‐strands. Abstract :